Hg selective adsorption on polypropylene-based hollow fiber grafted with polyacrylamide - Changkun Liu; Jizhen Jia; Ji’an Liu; Xiaoyan Liang (Adsorption Science & Technology)
A novel polypropylene hollow fiber membrane with a new function of selective adsorption of mercury ions in aqueous solutions was successfully prepared. The surface of the polypropylene hollow fiber membrane was initially modified with polydopamine by surface polymerization, and subsequently grafted with polyacrylamide (PAM) polymer brush via the surface initiated atom transfer radical polymerization (SI-ATRP) technique (thereafter named as PP-PAM). This study investigated the adsorption performance of Hg(II) ions by PP-PAM and the effect of various influencing factors on Hg(II) ion adsorption. The experiment indicated that the Hg(II) adsorption capacity of the PP-PAM increased with the increase of the pH, and the Hg(II) adsorption kinetics was consistent with the pseudo-second-order kinetic model. The adsorption isotherm followed the Langmuir model, with the maximum adsorption capacity calculated to be 0.854 mmol/g for Hg(II) ions. The adsorption study in multi-component system indicated that PP-PAM preferentially adsorbs Hg(II) over Pb(II) ions, with significant adsorption capacity difference of the two heavy metal ions. This study provided an efficient method for the preparation of the adsorptive polypropylene hollow fiber membrane, which expands its application for the selective removal of heavy metal ions.